Lithofacies, Facies Association, and Depositional Environment of 34-1, 33-6, and 33-4 Sandstone, Wida Field, Gita Member, Talang Akar Formation, Asri Basin, Offshore Southeast Sumatra - Saputra, Adi Danu; Surjono, Sugeng Sapto; Winardi, Sarju; Setyadi, Abdul Latif; Ralanarko, Dwandari (PROGRAM STUDI TEKNIK GEOLOGI FAKULTAS TEKNOLOGI MINERAL UPN VETERAN YOGYAKARTA, 2024)
Three Gita Member reservoirs 34-1, 33-6, and 33-4 produce from solution gas drive with rapid pressure decline and low recovery factor. After successful oil production enhancements through waterflooding injections prompt the need for a reservoir model in further field development. Before such models were built reservoir characterization was carried out to determine facies and depositional environment for facies modeling. The study integrated core, wireline log, petrophysical logs, seismic attribute, petrography, etc. Next, well correlation was carried out to distribute stratigraphic markers. Finally, seismic attribute and well correlation were integrated to construct pie chart and depositional environment map. External geometry from seismic attribute revealed distributary channel with point bars which act as reservoir and consist of medium-fine grained planar tabular cross bedding sandstone, mud drapes sandstone, and ripple-wavy lamination sandstone. The wireline log showed fining-upward pattern and core displayed abundant channel rip up clasts, sharp or erosional contact with underlying lithology. Frequent mud drapes found within channel sandstone indicate tidal influence in proximity to marine environment probably in lower delta plain. Channels are trending west-east (34-1) and north-south (33-6 and 33-4). Other facies associations are shallow marine, swamp, interdistributary bay, and tidally influenced interdistributary bay. Shallow marine FA consists of skeletal limestone (Lm), calcareous mudstone, and calcareous sandstone (Sc). Rootlet mudstone (Fb) and interlamination of carbonaceous mudstone with very fine-grain sandstone (Fl) formed interdistributary bay FA. Swamp FA consists of coal and coaly mudstone. Tidally influenced interdistributary bay FA consists of carbonaceous laminated mudstone high in carbon (Flb), intensely bioturbated carbonaceous mudstone (Flb), very finely laminated mudstone-very fine grain sandstone (Fl) and black fissile shale (Fm).